2012
DOI: 10.1007/s00134-011-2456-1
|View full text |Cite
|
Sign up to set email alerts
|

Time course of metabolic activity and cellular infiltration in a murine model of acid-induced lung injury

Abstract: This study demonstrated that PET imaging is a valid means of tracking the inflammatory response, also in longitudinal studies. Moreover, a correlation was found between persistence of the inflammatory response and fibrotic evolution of the injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…We used eight healthy mice as naïve controls as they did not receive any instillation into the main right bronchus, but they were ventilated and treated as the HCl instilled mice. Five mice only received "vehicle" (NaCl 0.9%) into the right main bronchus and they were killed 24 h after the instillation, as previous studies showed that this was the peak time of lung injury (8,39). Therefore the study included six groups of lungs: (1) injured (I) right lung; (2) contralateral noninjured (NI) left lung; (3) naïve control right lung; (4) naïve control left lung; (5) NaCl control right lung; (6) NaCl control left lung.…”
Section: Methodsmentioning
confidence: 99%
“…We used eight healthy mice as naïve controls as they did not receive any instillation into the main right bronchus, but they were ventilated and treated as the HCl instilled mice. Five mice only received "vehicle" (NaCl 0.9%) into the right main bronchus and they were killed 24 h after the instillation, as previous studies showed that this was the peak time of lung injury (8,39). Therefore the study included six groups of lungs: (1) injured (I) right lung; (2) contralateral noninjured (NI) left lung; (3) naïve control right lung; (4) naïve control left lung; (5) NaCl control right lung; (6) NaCl control left lung.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study demonstrated massive recruitment of neutrophils and macrophages into the lung that was associated with fibrotic evolution in a murine, HCl-induced lung injury model but the mechanisms involved were not investigated [28]. The present in vitro model mimics the in vivo conditions, and provides mechanistic insights demonstrating that the interaction of monocytes with the injured lung epithelial cells after HCl challenge accelerates the lung remodeling process.…”
Section: Discussionmentioning
confidence: 92%
“…Lung uptake of 18 F-FDG on PET is well recognized as a hallmark of ALI/ARDS [18,19,22,23]. 18 F-FDG uptake by the lungs and has been shown to correlate with neutrophil influx into the lungs in a variety of experimental pulmonary inflammatory lesions [21,26,27,32,33]. Previously we demonstrated, in a small clinical series, that diffuse lung uptake of 18 F-FDG PET was present 1–3 days prior to the point at which the clinical diagnostic criteria for ARDS were met [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods may be limited by heterogeneity in expression of biomarkers. Previous studies have indicated infiltration of neutrophils may represent the major component of 18 F-FDG uptake in lung parenchyma in ALI [26,27]. The goal of this study was to characterize the time course for pulmonary uptake of 18 F-FDG relative to neutrophil influx and to compare this to development of increased tomographic density (pulmonary edema) in a rat model of endotoxin (LPS)-induced ALI.…”
Section: Introductionmentioning
confidence: 99%